Assessment of Dental Arch Width Expansion Effectiveness Using a Novel Hybrid Aligner with Virtual Brackets and Nickel–Titanium Archwires: A Prospective Clinical Study - Jhonny Leon-Valencia; Jose Antonio Alarcon; Conchita Martin (Applied Sciences)
Objectives: This study aimed to evaluate the effectiveness of a novel hybrid aligner system, Geniova Technologies™ (GT), for arch expansion and to compare the predictability of its virtual setup with a conventional clear aligner system (CA) after the first treatment phase. Materials and Methods: Forty (mean age: 31.3 years for GT, 38.4 years for CA) adult patients with maxillary dentoalveolar compression and anterior crowding >3 mm were enrolled and assigned to GT and CA groups. Transverse changes for canines and premolars were measured at the cusp and cervical levels. Results: No significant baseline differences in transverse dimensions were found between groups. Treatment duration (4.25 months for GT vs. 9.75 months for CA) and the number of aligners (4.25 in GT vs. 28.25 in CA) significantly differed (p < 0.001). At the cusp level, mean transverse expansions for the maxillary first premolars were 2.78 mm (GT) and 2.44 mm (CA). However, effectiveness comparisons revealed no significant differences in expansion outcomes, with both groups showing similar accuracy. Conclusions: The GT group achieved comparable dentoalveolar expansion of canines and premolars in significantly less time and with fewer aligners than the CA group. The predictability of virtual setup measurements was similar for both systems, confirming their comparable performance in achieving planned expansion.